Management of gunshot trauma in the emergency room: A literature review (Research, Society and Development, 2025)
Introduction: The management of firearm trauma is a critical concern in emergency services due to its potential severity and complexity. Rapid identification and appropriate treatment are essential to improve patient outcomes. Objective: This article reviews current literature on best practices for managing gunshot trauma in the emergency department, highlighting effective interventions and treatment strategies. Method: A systematic review of the literature was carried out using databases such as PubMed, Google Scholar and Scopus. Studies published in the last ten years that address the management of penetrating trauma in emergency environments were included. Discussion: The literature highlights the importance of well-defined protocols, such as Advanced Trauma Life Support (ATLS), to guide initial treatment. Rapid assessment and control of bleeding are crucial. Interventions such as fluid resuscitation and blood transfusion are often necessary. The decision between immediate surgical treatment versus careful observation depends on the patient's stability and the location of the wound. Conclusion: Effective management of firearm trauma in the emergency department requires a multidisciplinary approach and well-established protocols. Continuous training of healthcare professionals is essential to ensure adequate implementation of best practices.